Implementing Online Learning Models to Strengthen Student Characteristics in Physics Education during the Covid-19 Pandemic - Diva Alkhadia Rana; Aulia, Lais Shifa; Reinhard Andrianus (ISEJ : Indonesian Science Education Journal, 2024)
The Covid-19 pandemic has significantly transformed higher education, shifting conventional face-to-face instruction to online learning and creating both challenges and opportunities for student development. This study aimed to analyze the implementation of online learning models and their influence on student characteristics in the Physics Education Study Program at Universitas Indraprasta PGRI. A descriptive qualitative approach was employed with purposive sampling of undergraduate students who had experienced online learning for at least two semesters, and data were collected through questionnaires, semi-structured interviews, and documentation. Thematic analysis was applied to identify patterns related to student learning strategies, the use of digital platforms, and character formation during online learning. The results revealed that students employed varied strategies such as mind mapping, blended learning, and group discussions via applications like WhatsApp, Zoom, and Google Classroom to sustain learning, while challenges included unequal internet access, limited technological facilities, and varying levels of readiness. Despite these obstacles, online learning contributed to the development of key character values, including independence, responsibility, discipline, and adaptability, which are essential in preparing students for the demands of the 21st century. The novelty of this study lies in its focus on the affective dimension of online learning, emphasizing character formation alongside cognitive achievement. The findings imply that universities and policymakers should design online learning systems that not only address technological barriers but also intentionally integrate character education to ensure holistic student development in future digital learning environments.